Citizenship and Its Role in Shaping National Identity - Yoni Lamtiur Silalahi; Immanuel Chioke; Sri Yunita (CV. Rayyan Dwi Bharata, 2025)
Citizenship is a multidimensional concept that establishes the formal and moral relationship between an individual and the state. Beyond its legal aspect, citizenship embodies a social, cultural, and political bond that shapes the identity and collective consciousness of a nation. In Indonesia, the notion of citizenship carries a profound meaning that integrates national ideology, moral values, and the principles of democracy derived from Pancasila and the 1945 Constitution. This article aims to explore the concept of citizenship, its legal foundations, the role of citizenship education in nation-building, and the contemporary challenges posed by globalization. The study employs a qualitative literature review by analyzing academic writings, legal documents, and previous research. The results indicate that citizenship serves not only as a legal framework but also as a moral compass that guides national identity, civic participation, and democratic integrity. Strengthening civic literacy and education is essential to nurture responsible, critical, and participatory citizens who can sustain national unity and sovereignty in the global era.